Congenital pulmonary airway malformation associated with mosaic Klinefelter syndrome. Issue 2 (30th September 2019) - Holubyeva, Anastasiya; Bracero, Luis A.; Feuerstein, Jessica L.; Bush, Steven
Abstract: A 26‐year‐old female, G4 P2012 presented for an anatomy scan at 18 weeks. Multiple macrocysts were seen in the left fetal lung, which lead to a diagnosis of congenital pulmonary airway malformation (CPAM) type II. A fetal MRI examination performed at 24 weeks of gestation confirmed the diagnosis of CPAM type II. A genetic amniocentesis was done to rule out a fetal chromosomal abnormality and the fetus was found to have mosaic Klinefelter syndrome. Fetal CPAM is not usually associated with chromosomal abnormalities unless there are other fetal malformations present. This is the first known case where a fetus with CPAM and no other malformation was found to have mosaic Klinefelter syndrome. Therefore, we believe it is prudent to offer prenatal diagnostic testing whenever a fetus with CPAM is identified with ultrasound.